Pengukuran Kecernaan Protein Kasar, serat Kasar, Lemak Kasar, dan Energi Pada Pakan Komersial Ikan Gurami (Osphronemus gouramy) dengan Menggunakan Teknik Pembedahan [Digestibility Value Of Crude Fiber and Nitrogen Free Extract (Nfe) for Different Commercial Feed In Gouramy (Osphronemus goramy Lac.) Using Surgical Technique] - Agustono Agustono (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Gouramy (Osphronemus goramy Lac.) belongs to a group of freshwater fish that have an important economic value and has been cultivated as other economic fish. Increase of biomass production in an aquaculture should consider feeding factors. Not every components in the feed can be absorbed in the digestive process. Parts that can not be absorbed by the body will be issued in the form of the feces so it can be determined the value of the digestibility of a feed material. Crude fiber and nitrogen free extract (NFE) digestibilty value is kind of nutrition that can be determinated. This study aims to determine the digestibility value of crude fiber and nitrogen free extract (NFE) in different commercial feed mills in gouramy (Osphronemus goramy Lac.). This study used 3 treatments, P1 ( commercial feed A), P2 (commercial feed B) and P3 (commercial feed C) with 6 replications. Digestibility value measurement method used was taking feces with surgical techniques. Feces retrieval method aims to minimize water contact with feces. The research design used in this study is completely randomized design. Observed variables are digestibility of crude fiber and nitrogen free extract (NFE). Based on the results of the study can be seen that in the used of diffetent commercial feed there is no significant difference (p> 0.05) on the digestibility value of crude fiber and nitrogen free extract.